Exploring the link between morphological bill traits and infestation by ectosymbionts in hummingbirds (Trochilidae) (2024)
Preening is a crucial aspect of avian behavior because it underpins the maintenance of feathers and the control of ectosymbionts, including ectoparasites. The bill, which evolved adaptively to perform different activities like self-defense, thermal regulation, and primarily feeding, also plays a key role in preening. The effectiveness of preening may be correlated with bill morphology, with some shapes (e.g.ong or highly decurved bills), presumed to be less effective. Given the remarkable diversity of bill morphologies among hummingbirds, we assessed the relationship between bill morphology and ectosymbiont infestation in this avian family. We obtained infestation data of ectosymbionts from 18 species of hummingbirds from Colombia representing diverse bill morphotypes and examined the relationship between bill shape and infestation by mites and lice in a phylogenetic context. We found that hummingbirds with straighter and deeper bills have higher ectosymbiont prevalence, including mutualistic mites and ectosymbionts in general. However, no significant relationship was found between bill shape and louse infestation independently. These findings suggest that bill shape, influenced by feeding-selective pressures, may impact preening effectiveness and thereby ectosymbiont loads, implying potential trade-offs in morphological adaptations. Further investigation is needed to evaluate other factors, such as additional morphological traits, preening behavior, and ecological factors, in predicting ectosymbiont loads.